2014
DOI: 10.3109/17483107.2014.974219
|View full text |Cite
|
Sign up to set email alerts
|

A home-based individualized information communication technology training program for older adults: a demonstration of effectiveness and value

Abstract: Building capacity of older adults to utilize the multifaceted potential of ICT is critical in addressing declines in health, impending disabilities, and social isolation. Implications for Rehabilitation A one-on-one home-based individualized information communication technology (ICT) training program for older adults could result in a progressive increase in the breadth of online activities carried out by them. Specifically, the increase in their usage of ICT could be expected in leisure-based online activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
72
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(78 citation statements)
references
References 28 publications
4
72
0
2
Order By: Relevance
“…In particular, technologies that can assist with maintenance of independence, physical and mental abilities are of interest, but the frustration associated with attempts to use technology as well as perceptions of a lack of assistance may be limiting factors (Heinz et al, 2013). Research has demonstrated the ability for older adults to successfully learn to use mobile technology, specifically tablet devices, with adequate training and support (Arthanat et al, 2014). Mobile technology has been utilised for health assessment (Bielli et al, 2004), health tracking (O'Brien et al, 2015) and behavioural intervention implementation (Kurti et al, 2015) among older adults with positive feedback from users.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, technologies that can assist with maintenance of independence, physical and mental abilities are of interest, but the frustration associated with attempts to use technology as well as perceptions of a lack of assistance may be limiting factors (Heinz et al, 2013). Research has demonstrated the ability for older adults to successfully learn to use mobile technology, specifically tablet devices, with adequate training and support (Arthanat et al, 2014). Mobile technology has been utilised for health assessment (Bielli et al, 2004), health tracking (O'Brien et al, 2015) and behavioural intervention implementation (Kurti et al, 2015) among older adults with positive feedback from users.…”
Section: Introductionmentioning
confidence: 99%
“…Therapists should assess older adults' priorities for using technology along with the wants and needs of the client to help individualize technological educational programs (Arthanat et al, 2016;Edgar et al, 2017). To identify client priorities, an excellent tool to use is the Canadian Occupational Performance Measure (COPM).…”
Section: Strategies For Teaching Students To Use Evidence-based Intermentioning
confidence: 99%
“…Technology is transforming the way occupational therapists (OTs) deliver healthcare to their clients, and entry-level OT students must be competent in using technology across the lifespan. Rapidly advancing technology has created a significant technology literacy lag in older adults, and OTs should address this lag by providing educational opportunities for older adults to use technology (Arthanat, Vroman, & Lysack, 2016). Entry-level OT faculty must prioritize technology education in instructional content related to older adults to help prepare students to implement technology into clinical practice (Arthanat et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations